2022
DOI: 10.1093/europace/euac210
|View full text |Cite
|
Sign up to set email alerts
|

P-wave duration and atrial fibrillation recurrence after catheter ablation: a systematic review and meta-analysis

Abstract: Aims Atrial fibrillation (AF) is a global health problem with high morbidity and mortality. Catheter ablation (CA) can reduce AF burden and symptoms, but AF recurrence (AFr) remains an issue. Simple AFr predictors like P-wave duration (PWD) could help improve AF therapy. This updated meta-analysis reviews the increasing evidence for the association of AFr with PWD and offers practical implications. Methods and results Publica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Previous research has identified various ECG parameters as predictors of incident AF as well as AF recurrence after ablation. 6–17 , 21 , 22 Especially the use of P -wave parameters has been suggested by the recent consensus document from the International Society of Electrocardiology for detection of pathological changes in atria and thereby AF risk stratification. 6 Indded, through an AI-based algorithm, a non-randomized, interventional trial also confirmed the utility of sinus rhythm ECG features in the selection of patients with high AF risk for screening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has identified various ECG parameters as predictors of incident AF as well as AF recurrence after ablation. 6–17 , 21 , 22 Especially the use of P -wave parameters has been suggested by the recent consensus document from the International Society of Electrocardiology for detection of pathological changes in atria and thereby AF risk stratification. 6 Indded, through an AI-based algorithm, a non-randomized, interventional trial also confirmed the utility of sinus rhythm ECG features in the selection of patients with high AF risk for screening.…”
Section: Discussionmentioning
confidence: 99%
“…Given the axis of Lead I running in parallel to Bachmann’s bundle, a reduction of PWV might, therefore, represent impaired conduction in Bachmann’s region, similarly to the proposed mechanism underlying IAB that has been linked to incident AF in previous studies. 15 , 21 , 22 For PWD and PR interval, Nielsen et al . 11 , 17 demonstrated a U-shaped relationship between both parameters and incident AF in the Copenhagen ECG Study of nearly 300 000 subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, in older patients, other poor ablation risk factors such as hypertension, obesity, and obstructive sleep apnea syndrome were higher. However, shorter preablation presence of these risk factors and easier lifestyle modifications after PVI in young patients may explain the differences with old patients [21,22] . Concerning complications, the overall complication rate was low.…”
Section: Discussionmentioning
confidence: 99%
“…P wave duration independently predicts AF recurrence after radiofrequency (RF) ablation. The risk of AF recurrence increases substantially with a P wave duration > 150 ms [47].…”
Section: P Wave Durationmentioning
confidence: 99%